The Influence of the “Other” in Psychotherapeutic and Medical Practice - Krumova-Pesheva, Rumyana; Peshev, Haralampi (Media and Language, 2020)
Professional interactions in psychotherapy and medicine are an important healing tool with a number of elements and particularities. The realtionship between the patient and the therapist is a structured relationship where a working alliance is built. The purpose of this paper is to present some of the characteristics of the impact on the other in the psychotherapeutic and medical communication. It is focesed on the methods of possible manipulation, which can take place on conscious and unconscious level. The manipulativeness of the approach is based on the influence of characteristics such as appearance, non-verbal behavior, tone of voice, sound of speech, etc. It is associated with certain suggestions for goodwill, security, privacy, community, authority, autonomy and more.